Non-Hodgkin's Lymphoma Presenting as an Isolated Vertebral Collapse - Agarwal, Vinay; Singhal, Namit; Chawla, Anu (Journal of Pediatric Neurology, 2018)
Non-Hodgkin's lymphoma (NHL) presenting as an isolated vertebral collapse is a very rare condition. We present a case of non-Hodgkin's lymphoma presenting as L3 vertebral body collapse on MRI. Isolated vertebral involvement was seen without evidence of any lesion elsewhere. Workup for systemic evidence of malignancy with contrast-enhanced CT of chest and abdomen did not reveal any other lesion. The patient was operated for L3 transpedicular decompression and L2–L4 pedicle screw rod fixation. Biopsy revealed diffuse large B cell lymphoma (DLBCL), NOS. Diagnosis was further confirmed by a postoperative PET scan, which showed multiple deposits in perinephric fat and retroperitoneal lymph nodes. Patient was treated with CHOP-based chemotherapy.
Keywords: non-Hodgkin's lymphoma; lymphoma; Pott's spine; vertebral collapse